DINAMIKA POLITIK PEMBANGUNAN PADA MASA ORDE BARU (Studi Tentang Industrialisasi Ketergantungan dan Peran Modal Jepang) - Beby Masitho (PERSPEKTIF, 2014)
Politic development Indonesia country at Orde Baru time to create industrializationhanging down, cause any problem can not to completion by Soeharto Politic rezim tomanage development project/ industrialization, inter problem is economy domesticstructure to colonial inheritance, so that industrial aspec, to be come problem atpowerless exsistantion bourgeois class in domestic. Horizontal design from grouping inbase culture for line (social stratification based on etnic line). Lame character indutrystructure with weaknes exsistance manufacture sectore cause high hanged at naturesource, as expore comodity and last domination strange capital in industry activity thatproductive.